Learning innovation in higher education: study of blended learning implementation at universitas islam labuhan batu - Amron Zarkasih Ritonga (12 Waiheru, 2025)
Blended learning is an innovative approach in higher education that integrates online and face-to-face instruction to enhance flexibility and student engagement. This study aims to examine the implementation of the blended learning model at Universitas Islam Labuhan Batu (UNISLA) and to evaluate its impact on student participation, academic achievement, and the challenges encountered during its application. A qualitative research method was employed, utilizing in-depth interviews, surveys, and document analysis involving students and lecturers. The findings reveal that implementing blended learning significantly enhances student engagement by offering diverse learning media and encouraging active participation in the learning process. Furthermore, students’ academic performance improved due to the flexibility in accessing learning materials at their own pace, which supports better comprehension and retention. However, the study also identifies several challenges, particularly the limited availability of digital infrastructure and uneven internet access, which hinder the full integration of online learning. These findings highlight the importance of institutional support and the strengthening of technological infrastructure to optimize the effectiveness of blended learning in higher education settings. This study contributes to the growing literature on digital learning in Indonesia and offers practical insights for educational institutions seeking to design adaptive and sustainable learning strategies.